Screening of Antibiotics Against β-amyloid as Anti-amyloidogenic Agents: A Drug Repurposing Approach - Alam, Jahangir; Jaiswal, Varun; Sharma, Lalit (Current Computer - Aided Drug Design, 2021)
Background: β-amyloid (Aβ) production and aggregation are the main culprits of Alzheimer’s disease (AD). There is no treatment available for halting the disease progression. Antibiotics are used not only to treat infections but also to some of the non-contagious diseases and have found active as anti-amyloidogenic agents. Objective: The aim of this work is to investigate anti-amyloidogenic activity of antibiotics as repurposing agents via inhibiting Aβ aggregation and fibril formation employing in silico and in vitro approaches. Methods: In silico screening was designed with receptor and ligand preparation, grid formation, docking simulation and its analysis. Thioflavin T-amyloid binding and protease-digestion studies were intended as in vitro assays. These methods assessed the pharmacological potential of antibiotics as anti-amyloidogenic agents. Results: Paromomycin and Neomycin were identified with a higher order of estimated free energy of binding in in silico experiments. In in vitro screening, paromomycin significantly (p<0.01) reduced the fluorescence intensity and resistance to tryptic degradation of Aβ(1-42) peptides while neomycin had no or little effect (p<0.01) when compared to control. Results from docking and wet lab studies were found in correlation. Conclusion: Paromomycin exhibited higher anti-Aβ aggregating and defibrillogenic activity than neomycin and left an indication for further in vivo testing and could be a future promising antiamyloidal candidate for the treatment of several amyloidoses.
Keywords: drug re-purposing